Tren penelitian kepemimpinan adaptif dalam pendidikan - Muhamad Mujari; Yuni Astuti; Priadi Surya (Universitas Pendidikan Indonesia, 2026)
Adaptive leadership has attracted scholarly attention for several decades; however, comprehensive studies that systematically map its development remain limited. This study aims to examine the evolution, research trends, and theoretical and practical contributions of adaptive leadership, with particular focus on educational management. This study employs a Systematic Literature Review approach combined with bibliometric analysis. A total of 463 publications from 1989 to 2025 were retrieved from the Scopus database using the keyword